Role of B cells in intratumoral MBTA immunotherapy of murine pheochromocytoma model - Uher, Ondrej; Hadrava Vanova, Katerina; Petrlakova, Katerina; Labitt, Rachael; Lencova, Radka; Frejlachova, Andrea; Ye, Juan; Wang, Herui; Masarik, Michal; Zenka, Jan; Zhuang, Zhengping; Pacak, Karel (Best practice & research. Clinical endocrinology & metabolism, 2025)
Immunotherapy represents a revolutionary advancement in cancer treatment, which has traditionally focused on T cells; however, the role of B cells in cancer immunotherapy has gained interest because of their role in antigen presentation, antibody production, and cytokine release. In this study, we examined the role of B cells in previously developed intratumoral MBTA therapy (mannan-BAM, TLR ligands, and anti-CD40 antibody) in murine models of MTT pheochromocytoma. The results indicated that B cells significantly enhance the success of MBTA therapy, with wild-type mice exhibiting a lower tumor incidence and smaller tumors compared with B cell-deficient mice. Increased IL-6 and TNF-alpha levels indicated severe inflammation and a potential cytokine storm in B cell-deficient mice. Neutralization of TNF-alpha ameliorated these complications but resulted in increased tumor recurrence. The results highlight the important role of B cells in enhancing the immune response and maintaining immune homeostasis during MBTA therapy. Our findings offer new insights into improving therapeutic outcomes.
Keywords: B cells; Adrenal Gland Neoplasms; Pheochromocytoma; intratumoral immunotherapy; pheochromocytoma; Interleukin-6; Immunotherapy; zvířata; myši; myši inbrední C57BL; B-lymfocyty; Mice; TNF-alfa; interleukin-6; B-Lymphocytes; Mice, Inbred C57BL; nádory nadledvin; melanoma; Tumor Necrosis Factor-alpha; Animals; cytokine storm; Disease Models, Animal; imunoterapie; feochromocytom; modely nemocí na zvířatech